Prospects of Developing Prefabricated Masonry Walling Systems in Australia - Julian Thamboo (Buildings, 2021)
Prefabrication has been shown to be an effective way of construction in the modern-day context. Although much progress has been made in developing reinforced concrete (RC), timber and steel prefabricated elements/structures, prefabrication of masonry walling systems has received limited attention in the past. Conventional masonry construction is labour-intensive and time-consuming; therefore, prefabrication can be an effective solution to accelerate the masonry construction to make it more cost-effective. Therefore, in this paper, an attempt has been made to evaluate the effectiveness of prefabricated masonry systems (PMS) in terms of their structural characteristics and sustainability perspectives in an Australian context. Subsequently, the available studies related to PMS and the prospects of developing prefabricated masonry walling systems were appraised and reported. In order to assess the applicability of PMS, a case study was carried out by designing four types of prospective prefabricated masonry walling systems for a typical housing unit in Australia. It was shown that the reinforced (RM), post-tensioned (PT) and thin layered mortared (TLM) masonry systems are better suited for prefabrication. Later, in order to assess the sustainability of the considered masonry walling systems, life cycle energy analyses were carried using the Environmental Performance in Construction (EPIC) database. It was found that there can be nearly 30% and 15% savings, respectively, in terms of energy saving and CO2 emissions in prefabricated construction than the conventional masonry construction. Finally, the prospects of developing PMS and the need for future research studies on these systems are highlighted.